PENGARUH UMUR BIBIT PINDAH TANAM DAN MACAM PUPUK DAUN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERONG (Solanum melongena, L.) VARITAS ANTABOGA 1 - Oky Ervina; Anjarwani Anjarwani; Historiawati Historiawati (Universitas Tidar, 2016)
The research about of the effect transplanting seedling and kinds of Foliar Fertilizer on the growth and yield of eggplant (Solanum melongena, L.) varitas antaboga 1 was conducted on 4 August to 11 December 2015 in Brengkel Village, Salaman District, Magelang. This research aim was to determine the age of seedling and leaf fertilizer which more right on the growth and yield of eggplant. The research method was used factorial experiment ( 4 X 3 ) by complete randomized block design. The first factor was the age of seedling transplating that consisted are 15, 20, 25 and 30 days. The second factor was foliar fertilizer Gandasil B, Topsil B and Neo Kristalon. The diversity test with the orthogonal polynomials for the first and LSD test for the second factor. The results shown that treatment of transplanting seedlings increase on height of plant, number of leaves, flowering age, fruit weight per plant, fresh weight of shoots, dry weight of shoots, fresh weight of roots, dry weight of roots but did not increase the number of fruits per plant. Foliar fertilizer increase height of plant, number of leaves, number of fruits per plant, fruit weight per plant, fresh weight of shoot, dry weight of shoot, fresh weight of roots, dry weight of roots and but did not increase flowering age.